Indian Writing in English and Issues of Visual Representation - Lau, Lisa. author. aut Link
X, 132 p.
Keywords: This book examines the use of book covers as marketing devices, asking what exactly they communicate to their readers and buyers, and what images they associate with a genre and create about a culture. Focusing on Indian women's writing in English, it combines the study of text with the study of materiality of the book.